A two-sector model with target-return pricing in a stock-flow consistent framework. Issue 3 (2nd July 2016) - Kim, Jung Hoon; Lavoie, Marc
ABSTRACT: In this paper, we build a generalized two-sector Kaleckian growth model and explore the dynamics towards long-run positions. The model incorporates conflicting claims of labour and firms over income distribution and endogenous labour-saving technical progress. Adopting a stock-flow consistent framework, our simulation experiments yield the following results. First, the 'paradox of thrift' and the 'paradox of costs' hold, meaning that lower saving rates generate higher growth rates while higher real wages generate higher profit rates, but the magnitude of the impact depends on the initial status of income distribution and monetary policy. Second, changes in autonomous labour-saving innovations might explain the phenomenon of the 'New Economy' of the second half of the 1990s within an alternative framework. Our simulations with a two-sector model retrieve the analytical results achieved with a one-sector Kaleckian model, with the addition of path dependence.